Breaking of Internal Waves and Turbulent Dissipation in an Anticyclonic Mode Water Eddy - Fernández-Castro, B.; Ebans, D. Gwyn; Frajka-Williams, Eleanor; Vic, C.; Naveira-Garabato, Alberto (Journal of Physical Oceanography, 2020)
22 pages, 13 figures.-- This article is licensed under a Creative Commons Attribution 4.0 license A 4-month glider mission was analyzed to assess turbulent dissipation in an anticyclonic eddy at the western boundary of the subtropical North Atlantic. The eddy (radius ≈ 60 km) had a core of low potential vorticity between 100 and 450 m, with maximum radial velocities of 0.5 m s−1 and Rossby number ≈ −0.1. Turbulent dissipation was inferred from vertical water velocities derived from the glider flight model. Dissipation was suppressed in the eddy core (ε ≈ 5 × 10−10 W kg−1) and enhanced below it (>10−9 W kg−1). Elevated dissipation was coincident with quasiperiodic structures in the vertical velocity and pressure perturbations, suggesting internal waves as the drivers of dissipation. A heuristic ray-tracing approximation was used to investigate the wave–eddy interactions leading to turbulent dissipation. Ray-tracing simulations were consistent with two types of wave–eddy interactions that may induce dissipation: the trapping of near-inertial wave energy by the eddy’s relative vorticity, or the entry of an internal tide (generated at the nearby continental slope) to a critical layer in the eddy shear. The latter scenario suggests that the intense mesoscale field characterizing the western boundaries of ocean basins might act as a “leaky wall” controlling the propagation of internal tides into the basin’s interior The MerMEED project was funded by the U.K. Natural Environment Research Council (NE/N001745/1). B. Fernández-Castro was supported by a Juan de La Cierva-Formación postdoctoral fellowship (FJCI-641 2015-25712) and a José Castillejo travel grant (CAS18/00017) by the Spanish Government. A. Naveira-Garabato was supported by the Royal Society and the Wolfson Foundation Peer reviewed